2009
DOI: 10.1097/mlr.0b013e318197b22a
|View full text |Cite
|
Sign up to set email alerts
|

Components of Care Vary in Importance for Overall Patient-Reported Experience by Type of Hospitalization

Abstract: The importance of patient experience dimensions differs substantially and varies by HT. Quality improvement efforts should target those aspects of patient experience that matter most for each HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 14 publications
10
74
1
3
Order By: Relevance
“…Furthermore, previous research demonstrated that differences in the conditions and/or treatments for which patients are hospitalized (which affect their interaction with staff and hospital resources) can also affect their inpatient satisfaction. 15 Therefore, we included a control for patients' underlying diagnosis in our analysis. Specifically, we defined 55 possible reasons for hospitalization using a combination of the standard 25 major diagnostic codes (MDCs) and the 2 service types (medical or surgical).…”
Section: Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous research demonstrated that differences in the conditions and/or treatments for which patients are hospitalized (which affect their interaction with staff and hospital resources) can also affect their inpatient satisfaction. 15 Therefore, we included a control for patients' underlying diagnosis in our analysis. Specifically, we defined 55 possible reasons for hospitalization using a combination of the standard 25 major diagnostic codes (MDCs) and the 2 service types (medical or surgical).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…2,[15][16][17][18][19] Various reasons have been posited for this, most having to do with the amount of time and interaction these care providers have with inpatient clients.…”
mentioning
confidence: 99%
“…However, the factors individual patients use to deem themselves satisfied remain largely unknown [3]. Studies found patient and visit characteristics as well as the outcome of care to be related to satisfaction ratings [4][5][6], but these findings are inconsistent and depend on the setting.…”
Section: Introductionmentioning
confidence: 96%
“…Da sich somit einige patientennahe versorgungsbezogene E-Health-Anwendungen primär als ergänzende Maßnahme zur Verbesserung der Versorgungsqualität oder des Krankheitsmanagements verstehen lassen, haben sog. PREs bei diesen Leistungen eine besondere Bedeutung [22,23].…”
Section: Patientenerlebenunclassified